A New Index for the Estimation of the Aromatic Character - IV - D'Auria, Maurizio (Letters in Organic Chemistry, 2014)
The new aromaticity index based on the energy of π orbitals D = [π1 +Σ2 n (π1 – πn )]0 /[π1 +Σ&2 n (π1 – πn)] × a , where n are the number of occupied πorbitals and a is the number of cycles in the molecule, was used in the calculation of the aromatic character of substituted pentaatomic heterocyclic compounds. Calculations have been performed on aromatic and heteroaromatic compounds by using DFT method at B3LYP/6-311+G(d,p) level. The D values were compared with those obtained performing the calculation of Aromatic Stabilization Energy (ASE) and Isomerization Stabilization Energy (ISE) of the same compounds. In all the cases, a good correlation has been found.
Keywords: DFT